Implementasi model think pair share dalam meningkatkan motivasi belajar siswa pada mata pelajaran Sejarah Kebudayaan Islam - Rahmah, Siti Muthia; Irfani, Fahmi; Asmahasanah, Salati (Program Studi Magister Pendidikan Agama Islam, 2025)
Islamic Cultural History (SKI) as a subject that contains historical and religious values needs to be delivered through an approach that encourages active student participation. However, observations at MAN 2 Bogor show low student motivation in SKI learning, which is influenced by the dominance of one-way lecture methods. This study aims to describe the implementation of the Think-Pair-Share (TPS) learning model in enhancing students' learning motivation in class XI A and to identify its supporting and hindering factors. The study employs a descriptive qualitative approach with data collection techniques including observation, interviews, documentation, and open-ended questionnaires. The results of the study indicate that the TPS model is able to increase students' activity, courage, cooperation, and interest in learning SKI. This model also creates a collaborative and enjoyable classroom atmosphere. Supporting factors include teacher planning and student involvement, while obstacles include time constraints and unequal participation. Therefore, the TPS model is suitable for implementation as an alternative learning strategy to enhance students' learning motivation in Islamic Cultural History lessons at madrasahs. Abstrak Sejarah Kebudayaan Islam (SKI) sebagai mata pelajaran yang memuat nilai-nilai historis dan religius perlu disampaikan melalui pendekatan yang mendorong partisipasi aktif siswa. Namun, hasil observasi di MAN 2 Bogor menunjukkan rendahnya motivasi belajar siswa dalam mengikuti pembelajaran SKI, yang dipengaruhi oleh dominasi metode ceramah satu arah. Penelitian ini bertujuan untuk mendeskripsikan implementasi model pembelajaran Think-Pair-Share (TPS) dalam meningkatkan motivasi belajar siswa kelas XI A serta mengidentifikasi faktor-faktor pendukung dan penghambatnya. Penelitian ini menggunakan pendekatan kualitatif deskriptif dengan teknik pengumpulan data berupa observasi, wawancara, dokumentasi, dan angket terbuka. Hasil penelitian menunjukkan bahwa model TPS mampu meningkatkan keaktifan, keberanian, kerja sama, dan minat belajar siswa dalam pembelajaran SKI. Model ini juga menciptakan suasana kelas yang kolaboratif dan menyenangkan. Faktor pendukungnya meliputi perencanaan guru dan keterlibatan siswa, sedangkan hambatannya adalah keterbatasan waktu dan ketimpangan partisipasi. Dengan demikian, model TPS layak diterapkan sebagai strategi pembelajaran alternatif dalam meningkatkan motivasi belajar siswa pada mata pelajaran SKI di madrasah.